1980
DOI: 10.1080/00913847.1980.11948564
|View full text |Cite
|
Sign up to set email alerts
|

Sportsmedicine Care in Chicago-Area High Schools

Abstract: Since few high schools have trainers on staff, Ms Porter studied the approach to injury management in 191 schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Although high schools have been encouraged to hire certified athletic trainers (ATs) to improve medical care, * no authors have examined whether a relationship between athletic training services and improved medical care actually exists in the high school setting. Additionally, evidence suggests that other factors, such as school size, 15,18,19,[24][25][26][27] a school's proximity to a medical center, 24,26 a school's public or private status, 5,15,21,23 a school's sports medicine supply budget, 15,17,33 a school's setting, 21,23 and the socioeconomic status of the students in a school, 5,21,23 may play a role in the medical care and coverage variations among high schools. Anecdotally, other factors, such as the success of a school's football program and the region of the state in which a school is located, have been linked to differences in the care given, although no evidence exists in the literature to support this claim.…”
mentioning
confidence: 99%
“…Although high schools have been encouraged to hire certified athletic trainers (ATs) to improve medical care, * no authors have examined whether a relationship between athletic training services and improved medical care actually exists in the high school setting. Additionally, evidence suggests that other factors, such as school size, 15,18,19,[24][25][26][27] a school's proximity to a medical center, 24,26 a school's public or private status, 5,15,21,23 a school's sports medicine supply budget, 15,17,33 a school's setting, 21,23 and the socioeconomic status of the students in a school, 5,21,23 may play a role in the medical care and coverage variations among high schools. Anecdotally, other factors, such as the success of a school's football program and the region of the state in which a school is located, have been linked to differences in the care given, although no evidence exists in the literature to support this claim.…”
mentioning
confidence: 99%
“…We found a few other national studies that have assessed physician and certified AT presence on the sideline. ‖ In 1980, Porter et al 26 looked at both private and public high schools and found that only 42.4% of schools had a physician on the sideline. When these investigators looked specifically at Chicago public high schools, physicians were found to be on the sideline 12.5% of the time and ATs 10% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that does exist is limited to isolated state-based or city-based analyses of practice. 10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] We are the first to describe national practice trends in secondary school athletic training.…”
Section: Discussionmentioning
confidence: 99%